New biocomposite material from ramie fibre and natural matrix of flee secretion on albasia tree as expansion effort of teaching material - Mujiyono Mujiyono (LPPM UNY, 2008)
Abstract: A biocomposite is a composite which consists of natural fiber as reinforcement and matrix as binder agents. Biocomposite materials are interesting phenomena because they are environmentally friendly, are renewable resources, and can increase the economic level of the neighbouring people. The objective of the present study is to look into the feasibility of biocomposite material from secretion of albasia flea as a binder agent and ramie fiber as reinforcement. Secretion of albasia flea was collected from Ciamisforest, WestJava, Indonesia with lumps type and then was reacted with methylated spiritus to liquefaction. Heating of the dilution offlea secretion at180°C in 15 minutes decreased the viscosity to become gel. The gels were layered on the surface of ramie fiber woven roving with the hand layout method. Molding of the biocomposite was done at 180-200°C in 10 minutes after 2-4 layers of ramiefiber were soaked with gel, pressing with pressure 40MPa, and cooling at room temperature in 4 hours. Density and tensile strengths of the biocomposite were evaluated with ASTM D638-90 standard and compared withpublicized biocomposites to know itsfeasibility. The tensile strength of the biocomposite from 60% of ramie fiber woven roving andsecretion of albasiaflea was 80 MPa with a density of 1.17g/cm'. This result showed that the biocomposite had a relatively higher tensile strength and lower density than an epoxy or polyester matrix. The biocomposite of the matrix of albasia flea secretion can become a novel material, have high feasibility based on availability of renewable resources, give simplicity of matrix processing, need no high technology on molding biocomposite, and have higher tensile strength relative to lower density. An implication of the results of the study can be in the development of new teaching material in the engineering material subject of study in the Faculty of Engineering of YogyakartaState University.Keywords: biocomposite, ramiefiber, secretion of .albasiaflea, natural matrix, tensile strength, density, binder agent, reinforcement